Revision of the Panurgus dargius Warncke, 1972 interpretation (Hymenoptera: Andrenidae), comparison with the morphologically close species - Patiny, Sébastien (Zootaxa, 2005)
The Panurgus dargius Warncke, 1972 description does not allow its unequivocal identification. This has led to several confusions, even in the Warncke determined series. An accurate updated description of the species is provided here, supplying a comparative diagnosis from closely related species and discussing subsequent changes.